Assessment of the Effect of Pharmacotherapy in Common Cold/Acute Bronchitis – the Bronchitis Severity Scale (BSS) - Kardos, P.; Lehrl, S.; Kamin, W.; Matthys, H. (Pneumologie, 2014)
Background: Acute bronchitis (AB) is a highly contagious infection of the airways, presenting mostly in connection with common cold (CC). There is a high variance in duration and course of symptoms which, sooner or later, also may disappear spontaneously and change during the course of the disease. Therefore, assessment of treatment outcome is difficult.Methods: Composite outcome measures are commonly used to examine the effects of pharmacotherapy in complex diseases. We discuss the features of the Bronchitis Severity Scale (BSS) on the basis of the available literature.Results: For the BSS the five most important symptoms of AB are rated by the patient and the physician. Since its introduction in 1996, the BSS has been used in many clinical trials evaluating treatment effects of AB. Its score correlates well with clinical findings. As thorough validation analyses revealed, this applies even more to the BSS subscales “cough domain” and “sputum domain”.Conclusion: The validated BSS appears to be a reliable tool to assess therapeutic effects in CC/AB. The BSS and its subscales are recommended as outcome measures for future drug trials in CC/AB, but also help physicians to focus their consultation in patients with CC/AB.